Laryngeal Cancer in Srinagarind Hospital - Ratana – anekchai, Teeraporn; Vatanasapt, Patravoot; Art-smart, Thumnu (Srinagarind Medical Journal, 2013)
Background : laryngeal cancer is the common cancer in ENT practice. According to tumor registry of Srinagarind Hospital, it is the third most common cancer of upper G-I & Respiratory tract cancer being after oral and nasopharyngeal cancer. Additionally it had never been reported in Srinagarind Hospital. Objective : Study about character of laryngeal cancer and its treatment Design : Retrospective, descriptive study Setting : Srinagarind Hospital, Khon Kaen University Subject : Patients whose diagnosed as squamous cell carcinoma of the larynx and were treated in srinagarind Hospital since 1993-1997. Results : There were 59 cases included in this study. Fifty-eight cases were male and average age was 63 years old. The most common type was supraglottic cancer (44%) following by glottic cancer (31%) and most cases 76%) were advanced cases, most (55%) were treated by surgery with postoperative radiation following by primary radiation (32%). Three of nine cases whom received neck dissection have positive malignancy in neck node specimen. Summary : Most of laryngeal cancers were advanced stage that need a combined treatment (surgery with postoperative radiation) as the most common treatment option.